2009
DOI: 10.1108/00012530910932302
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of scientific co‐authorship in Spanish universities

Abstract: Purpose -The purpose of this paper is to visualize the inter-university and international collaboration networks generated by Spanish universities based on the co-authorship of scientific articles. Design/methodology/approach -The approach takes the form of formulation based on a bibliometric analysis of Spanish university production from 2000 to 2004 as contained in Web of Science databases, applying social network visualization techniques. The co-authorship data used were extracted with the total counting me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
1
14
0
8
Order By: Relevance
“…For instance, a microanalysis of inter-institutional co-authorship networks comprising universities, government and private companies located in Madrid, Spain, is proposed in [25]. This study was later extended to the rest of Spanish Universities in [21]. Authors concluded that Spanish inter-university collaboration patterns appear to be influenced by both geographic proximity and administrative and political affiliation, which is in line with some other previous studies.…”
Section: Related Worksupporting
confidence: 68%
See 1 more Smart Citation
“…For instance, a microanalysis of inter-institutional co-authorship networks comprising universities, government and private companies located in Madrid, Spain, is proposed in [25]. This study was later extended to the rest of Spanish Universities in [21]. Authors concluded that Spanish inter-university collaboration patterns appear to be influenced by both geographic proximity and administrative and political affiliation, which is in line with some other previous studies.…”
Section: Related Worksupporting
confidence: 68%
“…The application of social network analysis to a coauthorship networks scenario has become increasingly common during the last decade [21]. They share with other social networks global topological properties such as small world-property, long-tail degree distribution and a scaling law for the clustering coefficient [22].…”
Section: Related Workmentioning
confidence: 99%
“…A forte participação dos EUA pode ser associada à proeminência daquele país como zona central da ciência e à liderança exercida no campo científico (Mueller & Oliveira, 2003), embora também indique certa dependência na produção científica. Na perspectiva da internacionalização da ciência, a colaboração com os EUA pode elevar a visibilidade das publicações e ampliar seu impacto na comunidade científica internacional, embora o processo de internacionalização também exija diversificação de parceiros e simetria nas relações de colaboração (Olmeda-Gómez et al, 2009;Sebastián, 2011).…”
Section: Colaboração Internacionalunclassified
“…Furthermore, comparative citation frequencies of one data set support the view that collaborative research produces significantly more authoritative research, as being more cited through a longer lifetime (Beaver 2004). Also, the quality of the international articles is much better than of the national papers (Klaić and Klaić 2004;Olmeda-Gómez et al 2009), especially when considering the articles from less developed I. Vilibić (&) Institute of Oceanography and Fisheries, Š etalište I. Meštrovića 63, 21000 Split, Croatia e-mail: vilibic@izor.hr countries (Russel 1998;Bouabib and Martin 2009).…”
Section: Introductionmentioning
confidence: 69%